Crosslinkable metal chelate as the electron transport layer for efficient and stable inverted polymer solar cells. (13th August 2020) - Liu, Hao; Ma, Zongwen; Yu, Runnan; Gao, Huaizhi; Lin, Jun; Hayat, Tasawar; Alsaedi, Ahmed; Tan, Zhan'ao
Abstract : Efficient inverted polymer solar cells with crosslinked Hf(ACBV)4 as the ETL are demonstrated, exhibiting excellent operation stability under 20 hours continuous illumination in air. Abstract : A novel crosslinkable acetylacetone chelate, Hf(ACBV)4, was designed and synthesized using 1, 3-bis(4-vinylphenyl)propane-1, 3-dione (ACBV) and hafnium chloride (HfCl4 ). The obtained crosslinked chelate film exhibits excellent solvent-resistance property and was successfully applied as the electron transport layer in inverted polymer solar cells (PSCs). The crosslinking property was proved by differential scanning calorimetry (DSC) measurements and the unchanged UV-visible absorption of the crosslinked film after washing with chloroform. The obtained crosslinked Hf(ACBV)4 film can effectively ameliorate the contact between ITO and the photoactive layer, facilitating the charge transfer process of the device. Moreover, the devices based on PM6:Y6 achieved an efficiency of 15.17% and exhibited excellent stability with 90% retention efficiency after 20 h of continuous illumination in air. Our work demonstrates a new approach in designing effective crosslinkable chelates as ETLs to improve the stability and efficiency of PSCs.